An analysis of Obama’s Speech at climate Change Conference COP 21 in Paris in 2015 Using Fairclough’s Three-Dimensional Model - rukman rukman (Jurnal Sosioteknologi, 2016)
The aim of this paper is to analyze Obama’s speech at climate change conference (COP 21) held in Paris November 18, 2015. The analysis uses Fairclough’s three-dimensional model The three-dimensional model includes such aspects as text (language), discursive practice, and social practice. The results of analyzing these aspects show that under the textual (language) aspect, this speech is dominated by the use of both the imperative mood and material process of transitivity. Under the discursive practice, the speech blends the discourse of long-term commitment in achieving the two degree Celsius global warming target with the discourse of innovation and investment in clean energy technologies. As for its social practice, the speech reflects the shifting from the discourse of climate change into the discourse of innovation and investment in clean energy. Keywords: Fairclough’s three-dimensional model, imperative mood, transitivity, climate change (global warming) discourse, clean energy technology innovation and investment discourse